THE EFFECT OF FOLIC AND SALICYLIC ACID ON GROWTH OF COTTON (Gossypium hirsutum L.) UNDER DROUGHT CONDITIONS - Mohammed Basheer Ismael; Diaa Ayoub Ibrahim (Science Journal of University of Zakho)
This study was performed between February and August 2023 at a local farm affiliated with the Biology Department, College of Science, University of Zakho, Kurdistan Region, Iraq. It aimed to assess the influence of drought stress and the foliar application of salicylic and folic acid on certain growth parameters of two cotton cultivars (MAY 505 and MAY 455). A factorial experiment in the form of randomized complete block design (RCBD) was employed to evaluate the response of growth parameters of cotton cultivars to three concentrations of salicylic acid (0, 1, and 2 mM) and folic acid (0, 5, and 10 mM), either individually or combined, under different irrigation regimes. Additionally, the two cultivars were subjected to three different irrigation regimes: continuous irrigation (Ci), 10-day drought, and 15-day drought. The findings revealed significant differences in shoot length, branch number, longest branch length, leaf surface area, and flower number among cultivars, drought treatments, and spray treatments. Cultivar MAY505 consistently outperformed MAY455 in terms of growth parameters. Moderate drought stress (10 days) slightly enhanced shoot length, while prolonged drought significantly reduced general growth. Foliar application of Salicylic acid (SA) and Folic acid (FA), particularly the combination of 2 mM SA + 10 mM FA, significantly increased shoot length, branch number, and flower number in both cultivars. However, the response to folic and salicylic acids varied between cultivars. These findings suggest that cultivar selection and appropriate foliar spray applications can mitigate the adverse effects of drought stress on cotton plant growth and yield. Further research is needed to elucidate the underlying physiological mechanisms responsible for these responses and to optimize the use of foliar sprays for sustainable cotton production under water-limited conditions.